2013
DOI: 10.3390/ph6010070
|View full text |Cite
|
Sign up to set email alerts
|

Clevidipine for Perioperative Blood Pressure Control in Infants and Children

Abstract: Various pharmacologic agents have been used for perioperative BP control in pediatric patients, including sodium nitroprusside, nitroglycerin, β-adrenergic antagonists, fenoldopam, and calcium channel antagonists. Of the calcium antagonists, the majority of the clinical experience remains with the dihydropyridine nicardipine. Clevidipine is a short-acting, intravenous calcium channel antagonist of the dihydropyridine class. It undergoes rapid metabolism by non-specific blood and tissue esterases with a half-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…8,9 The first study outlined the use of clevidipine preoperatively, intraoperatively, and postoperatively in doses ranging from 0.5 to 3.5 mg/kg/min in a cohort of 10 patients, ranging in age from 9 to 18 years. 8,9 The first study outlined the use of clevidipine preoperatively, intraoperatively, and postoperatively in doses ranging from 0.5 to 3.5 mg/kg/min in a cohort of 10 patients, ranging in age from 9 to 18 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 The first study outlined the use of clevidipine preoperatively, intraoperatively, and postoperatively in doses ranging from 0.5 to 3.5 mg/kg/min in a cohort of 10 patients, ranging in age from 9 to 18 years. 8,9 The first study outlined the use of clevidipine preoperatively, intraoperatively, and postoperatively in doses ranging from 0.5 to 3.5 mg/kg/min in a cohort of 10 patients, ranging in age from 9 to 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…9 Clevidipine was administered as either a continuous infusion or as a bolus dose. 9 Clevidipine was administered as either a continuous infusion or as a bolus dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It undergoes rapid metabolism by non-specific blood and tissue esterases, and therefore no dosing adjustment is required in those with renal or hepatic impairment [21]. Adult trials have demonstrated its efficacy in rapidly controlling BP in various clinical settings with a favorable adverse effect profile [22]. Because it is prepared in a lipid solution, it is contraindicated in those with egg and soy allergy as well as those with lipid disorders [3, 23].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Because it is prepared in a lipid solution, it is contraindicated in those with egg and soy allergy as well as those with lipid disorders [3, 23]. One retrospective report included 14 pediatric patients, 11 months to 15 years old, undergoing surgery for congenital heart disease [24]. In 6 patients, it was administered as a continuous infusion for postoperative HTN; in 5 patients, a bolus dose for HTN during emergence from anesthesia; in 3 patients, it was given as continuous infusion for intraoperative BP control during cooling and cardiopulmonary bypass.…”
Section: Treatment Optionsmentioning
confidence: 99%